Probiotic cheese as a functional food - MAZLUM, Halit; ATASEVER, Mustafa (Asian-Australasian Journal of Food Safety and Security, 2023)
Nutrition style and preference is one of the priority issues on which health-protective and disease-preventive measures are taken for a healthy life. For this purpose, functional foods that show beneficial effects on health as well as the nutrional value have become increasingly important. Among functional foods, probiotic foods which are produced by using probiotic microorganisms constitute the most important and interesting group. In order for a probiotic food to show its beneficial effect on health, it must contain minumum 106-107 cfu of microorganisms in grams or mililitres during its shelf life. Milk and dairy products are the foods in which probiotics are commonly used. However, the development of probiotic dairy products seems to focus on fermented milk (e.g., kefir) and yoghurt. Cheese has more advantages over fermented milk or yoghurts as a carrier food to intestinal environment due to the fact that it has a low oxygen content, high pH, high fat content and a firmer texture. In this review, the general characteristics of functional foods and probiotics are explained and evaluations are made using the potential of cheese as a probiotic carrier product. This study can shed light on new studies on the use of cheese as a functional probiotic food. Asian Australas. J. Food Saf. Secur. 2023, 7 (1), 20-32